2004
DOI: 10.1590/s0103-90162004000400012
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and callogenesis of Curcuma zedoaria Roscoe

Abstract: Curcuma zedoaria Roscoe (zedoary) is a medicinal properties-bearing Zingiberaceae from which rhizomes are commercially exploited. The objective of this work was to establish an in vitro protocol for micropropagation and callogenesis of Curcuma zedoaria Roscoe as alternative to improve plant production, turning economically feasible the exploitation of its secondary metabolites which present medicinal properties. Micropropagation by using shoot apexes produced by rhizome and from in vitro plants were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…This shows an inhibitory effect of NAA auxin (in the concentrations used in this work) on the organogenesis of the species under analysis. Similar results were found for Curcuma zedoaria Roscoe (Miachir et al, 2004) and four species of the genus Watsonia (Ascough et al, 2007).…”
Section: Resultssupporting
confidence: 78%
“…This shows an inhibitory effect of NAA auxin (in the concentrations used in this work) on the organogenesis of the species under analysis. Similar results were found for Curcuma zedoaria Roscoe (Miachir et al, 2004) and four species of the genus Watsonia (Ascough et al, 2007).…”
Section: Resultssupporting
confidence: 78%
“…All the successful induction of callus in this study were obtained in 2, 4-D + BAP supplemented MS media. 2, 4-D alone failed to induce calluses at all the concentration tested (0.5, 1….3 mg/L) which was in line with the report of Zuraida et al, (2014) in C. caesia and also with the finding of Miachir et al, (2004) and Tuan et al, (2011) in C. zedoaria, however, in contradiction to the finding of Saensouk, (2011) were similar and differed from all others (p <0.05). Equal and higher concentration 2,4-D + BAP of 5 mg/L each, responded well (40.00%) to callus induction in contrast to the finding of Taha et al, (2013) who reported higher concentration of 2,4-D up to 4 mg/L in combination with 0.2 mg/L BAP to have performed less in the in vitro culture of Zingiberofficinale using leaves explants.…”
Section: Resultssupporting
confidence: 85%
“…1955). This shows that the conventional multiplication capacity of C. longa is very limited compared to other propagation methods (Miachir et al, 2004).…”
Section: Introductionmentioning
confidence: 94%